Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-beta zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
The sulfonated H-beta zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) fromD-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N-2 physisorption, NH3-temperature programmed desorption and carbon-hydrogen-nitrogen-sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-beta (S-beta) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-beta catalyst at 160 degrees C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-beta; HMF; levulinic acid; sulfonated zeolite; yield

Milder operating parameters for one-step conversion of fructose to levulinic acid over sulfonated H-β zeolite in aqueous media - Bisen, Swapneel K.; Niphadkar, Prashant S.; Nandanwar, Sachin U.; Simakova, Irina; Bokade, Vijay V. (Environmental Progress & Sustainable Energy, 2021)
Abstract The sulfonated H-β zeolite was successfully prepared and used for the synthesis of levulinic acid (LA) from D-fructose. The catalyst was characterized by powder X-ray diffraction, Fourier transform infrared spectroscopy, scanning electron microscope, N2 physisorption, NH3-temperature programmed desorption and carbon–hydrogen–nitrogen–sulfur analysis. The total acid amount is increased with increase in sulfur loading, confirmed that the sulfonic acid group (SO3-H) is successfully grafted onto zeolite structure. The various parameters such as different amount of sulfur loading, reaction temperature, time, catalyst loading was studied for selective production of LA. The catalytic activity of sulfonated H-β (S-β) zeolite was found to be efficient for synthesis of LA from D-fructose in aqueous media. Maximum LA yield of 43.5 mol%, low HMF yield (<1%) with 98.15% fructose conversion was obtained with 3% S-β catalyst at 160°C for 7 hr. The catalyst was reusable for minimum three times by H2O2 regeneration. This study provides the new zeolitic catalyst for the efficient production of LA at shorter reaction time (7 hr) and low catalyst to substrate ratio (0.7:1).
Keywords: conversion; D-fructose; H-β; HMF; levulinic acid; sulfonated zeolite; yield

Methanol-to-light olefins reaction using Zn-Ag modified SSZ-13 catalyst - Dange, Rutvija M.; Gawali, Chirag B.; Niphadkar, Prashant S.; Bokade, Vijay V.; Nandanwar, Sachin U. (ChemistrySelect, 2022)
The 2 wt.% of Zn and Ag (Zn1-x-Ag-x; x=0.2, 0.4, 0.6 %) modified SSZ-13 (SZ-13) zeolite was prepared by wet-impregnation method, and its catalytic activity was demonstrated for methanol-to-olefin (MTO). The Zn-0.6-Ag-0.4/SZ-13 catalyst exhibited high catalytic activity due to change in properties of catalyst. The Zn particles were highly dispersed inside the SZ-13; while Ag particles were dispersed on the surface of SZ-13, confirmed by HRTEM and surface area. The small % of Ag over SZ-13 promotes ethylene production via aromatization of reaction, and highly dispersed Zn on SZ-13 help to produce stable ethylene and propylene. The Zn-0.6-Ag-0.4/SZ-13 catalyst showed (similar to 10 %) higher light olefin (87 %) selectivity than parent SZ-13 as well as mono metal incorporated SZ-13. The higher catalytic activity was attributed due to effect of both metals (Zn and Ag), where Ag promotes partial aromatization on the surface, and Zn increases the Lewis acidity in the zeolite pore. This catalyst can help to improve the selectivity of light olefin using MTO reaction.
Keywords: Ethylene; Methanol-to-Olef; Propyl; Silver; SSZ; zinc